2013
DOI: 10.1371/journal.pone.0076761
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neuroblastoma Stem Cells with Retinoic Acid and Proteasome Inhibitor

Abstract: BackgroundNeuroblastma cell lines contain a side-population of cells which express stemness markers. These stem-like cells may represent the potential underlying mechanism for resistance to conventional therapy and recurrence of neuroblastoma in patients.Methodology/Principal FindingsTo develop novel strategies for targeting the side-population of neurobastomas, we analyzed the effects of 13-cis-retinoic acid (RA) combined with the proteasome inhibitor MG132. The short-term action of the treatment was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
4
47
0
1
Order By: Relevance
“…Previous studies have demonstrated that RAinduced differentiation can cause cell cycle arrest either in G1/G0 phase or in G2/M phase and a decrease in proliferation rates, which leads to terminal differentiation of neuroblastoma cells (Qiao et al 2012;Hämmerle et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that RAinduced differentiation can cause cell cycle arrest either in G1/G0 phase or in G2/M phase and a decrease in proliferation rates, which leads to terminal differentiation of neuroblastoma cells (Qiao et al 2012;Hämmerle et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma cell lines were commonly used to demonstrate the differentiation and anti-tumorigenic potential of RA. LA-N-1/2/5, CHP-134, KA [210,211], SH-SY5Y [212], Neuro-2a [213], SK-N-BE2 [214], IMR-32 [215], SMS-KCNR [216], and D283 [217] can all be differentiated by retinoids into cells expressing neuronal markers and exhibiting neurite morphology. Although many cell lines can be differentiated in response to RA, the clinical response to RA treatment is variable.…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…In order to identify the metabolic events occurring during neuronal precursor differentiation, the glucose and lipid metabolism was followed in a recognized model of neuronal differentiation in vitro, the SH-SY5Y neuroblastoma cell line, which presents, according to literature, a subpopulation of stemlike cells expressing nestin and SOX2. 26 In the same model, considering its role in glucose and lipid metabolism and its involvement in NSCs maintenance, the PPARg isotype was specifically investigated. Moreover, in order to gain more insight into PPARg distribution also in situ, and considering the difficulties to obtain adult human normal brain specimens, the immunolocalization of PPARg in adult mouse brain SVZ was also studied.…”
Section: Introductionmentioning
confidence: 99%